2014
DOI: 10.1111/hiv.12180
|View full text |Cite
|
Sign up to set email alerts
|

Improved serum cholesterol in paediatric patients switched from suppressive lopinavir‐based therapy to boosted darunavir or atazanavir: an 18‐month retrospective study

Abstract: Boosted protease inhibitor (PI)-based antiretroviral therapy (ART) in children with perinatally acquired HIV (PaHIV) infection typically includes lopinavir co-formulated with ritonavir (LPV/r), which is the preferred PI according to the 2009 Paediatric European Network for the Treatment of AIDS (PENTA) guidelines [1]. PIs adversely affect lipid parameters, and data from adult studies suggest that alternative once-daily boosted PIs may have more favourable lipid profiles compared with LPV/r [2,3]. While a switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Our results are consistent with those of studies in treatment‐naïve HIV‐infected adults, which have shown improved metabolic parameters with newer PIs . Few studies, however, have been published in the paediatric HIV‐infected population on longitudinal lipid changes over time with newer PIs such as ATV/r and DRV/r, and most have been limited by small sample sizes . Similar to our findings, a case series of HIV‐infected children who switched from lopinavir/r to ATV/r or DRV/r reported a significant reduction in TC at 18 months post switch compared with baseline levels, but no changes in TG, HDL‐C or LDL‐C .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with those of studies in treatment‐naïve HIV‐infected adults, which have shown improved metabolic parameters with newer PIs . Few studies, however, have been published in the paediatric HIV‐infected population on longitudinal lipid changes over time with newer PIs such as ATV/r and DRV/r, and most have been limited by small sample sizes . Similar to our findings, a case series of HIV‐infected children who switched from lopinavir/r to ATV/r or DRV/r reported a significant reduction in TC at 18 months post switch compared with baseline levels, but no changes in TG, HDL‐C or LDL‐C .…”
Section: Discussionsupporting
confidence: 91%
“…Few studies, however, have been published in the paediatric HIV-infected population on longitudinal lipid changes over time with newer PIs such as ATV/r and DRV/r, and most have been limited by small sample sizes [27][28][29]. Similar to our findings, a case series of HIV-infected children who switched from lopinavir/r to ATV/r or DRV/r reported a significant reduction in TC at 18 months post switch compared with baseline levels, but no changes in TG, HDL-C or LDL-C [29]. Children in the Darunavir EvaLuation in Pediatric, HIVInfected, treatment-experienced patients (DELPHI) trial begun on darunavir demonstrated decreases in TG levels 48 weeks post-initiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Switching to once‐daily boosted PIs has been associated with improved lipid profiles in adult studies and now this has been demonstrated in a paediatric population 196.…”
Section: When To Switch Resistance Testing and Second And Subsequentmentioning
confidence: 97%
“…Previous studies have suggested that using LPV/r can enhance renal toxicity of tenofovir and LPV/r is associated with renal dysfunction (11,12). Depending on the situation, substitution of other protease inhibitors, such as ritonavir-boosted darunavir or integrase inhibitors, for LPV/r can be used as salvage regimens (13). If this is not possible because of budget limitations, lipid-lowering therapy can be beneficial in people who are taking LPV/r with known risk factors, including older age, HT, and diabetes mellitus (14-18).…”
Section: Resultsmentioning
confidence: 99%